216k views
3 votes
Solve the equation below 4(ax + 3) -3ax = 25 + 3.

User Graham T
by
6.4k points

2 Answers

4 votes

Answer:

4(ax + 3) -3ax = 25 + 3

4ax + 12 - 3ax = 25 + 3

4ax - 3ax + 12 = 28

1ax + 12 = 28

1ax = 28 - 12

ax = 16

a = 16/x

x = 16/a

User Jordan Medlock
by
5.4k points
1 vote

Hey there!

4 (ax + 3) - 3ax = 25 + 3

4ax + 12 - 3ax = 28

4ax - 3ax = 28 - 12

ax = 16.

Solving for 'a'

ax = 16

a = 16/x

Solving for 'b'

ax = 16

x = 16/a

Hope it helps ya!

User Benjamin
by
5.8k points